The South China Sea dispute and its economic implications - Tan, Kimberley Zhao Xin (2017)
This paper will study on the economic implications brought about by the SCS dispute. This is because SCS sees more than $5 trillion worth of trade passing through, has a rich biodiversity as well as oil and gas reserves. Any shift in balance of power in the politically sensitive region will have significant impacts on international trade, fishing rights and E&P activities. Thus, the study of economic implications will be broken down into three parts: trade routes, fishing rights and oil and gas industry. At present, trade routes are open and commercial vessels are free to access it. As China is ambitious in its island building campaigns and placing military equipment there, there is no certainty that China may keep them open after gaining control of the region. The closure is detrimental to international trade as fleets have to reroute, resulting in increased costs and upsetting tonnage demand and supply in the long run. Singapore is also likely to no longer be crowned as the region’s oil hub port when tankers reroute and does not go through Straits of Malacca. Fishing has been a valuable resource to many surrounding coastal states, either as exports or as nutrients for their population. However, China is the main culprit for overfishing and depleting fishstocks, and even spreading this problem to other places when they poach in others’ waters. Factors that contribute include use of destructive trawlers, heavy subsidies and militarising of fishing vessels by the government. Therefore, to alleviate the problem, a ban on trawlers can be introduced to preserve the natural ecosystems and subsidies reduction, demilitarising fishing vessels and imposing fishing restrictions help to reduce catch. The SCS’ oil reserves are unable to feed the region, hence countries will increase oil imports in the future. As for the abundant gas reserves, the costly gas E&P projects will limit the domestic production, thereby forcing the countries to import as means of a viable option to fill the demand gap. Amongst the growing LNG trade region, Singapore can also make use of the chance to establish itself as the region’s next gas hub port.